IMPLEMENTASI METODE BERMAIN PERAN DALAM PROSES PERKEMBANGAN SOSIAL ANAK USIA DINI DI KELOMPOK B (UNISMA, 2021)
Method is a method used in completing a job or problem. The learning method is a method used by a teacher in delivering learning. There are various methods, one of which is the role playing method. The role playing method is a method with the characteristics of playing a character or becoming an object. As stated by Santoso (2011), role playing is dramatizing and expressing one's behavior, expressions, and movements in social relationships. As a method of role playing method, it certainly has advantages and disadvantages as well as supporting and inhibiting factors. One of the supporting and inhibiting factors is of course the teacher's expertise and mastery in applying the role-playing method. Therefore, it takes understanding and creativity of teachers in the learning process with the role playing method.